ANALISIS DAN PEMODELAN PELIMPAHAN PERKARA PIDANA MENGGUNAKAN BUSINESS PROCESS IMPROVEMENT (Studi Kasus: PENGADILAN NEGERI XYZ) - Dudi Awalludin (Faktor Exacta, 2022)
In line with the progress of the times with the progress of developing science and technology, computers are not only used as business data development tools but also use means of processing data data quickly, accurately, and systematically. At present the business process system in Criminal Case Delegation at the XYZ District Court is still ineffective in the case registration approval process. In the trial of receiving a case transfer from the Public Prosecutor there were still some shortcomings, often double checking, there was no sign of court thanksgiving when it was transferred to the Young Criminal Registrar so that it could not be controlled again. Based on the problems obtained, the study analyzed existing transitions using qualitative using Business Process Improvement (BPI) and modeled using Business Process Modeling Notation (BPMN). to see in terms of internal and external factors. After analysis, make a checklist and receipt when delegating it to the Young Registrar of Criminal agar in the process of transferring a controlled file. Therefore, with the approval of the checklist, it can save time in performance.